Digital Inequality and Social Stratification in the Era of Platform Society: A Sociological Analysis of Urban Youth in Indonesia. - Ahmad Mubarok (PT. AVID MEDIA INDONESIA, 2026)
This study examines the relationship between digital inequality and social stratification in the context of platform society among urban Indonesian youth using a qualitative interpretive approach with a critical-constructivist paradigm. Through a multi-site case study in South Jakarta, North Jakarta, and Depok with 30–40 informants aged 18–30 years, data were collected via in-depth interviews, participant observation, focus group discussions, and document studies. Data were then analyzed using thematic analysis, Fairclough's critical discourse analysis, and Bourdieu's field analysis. The findings reveal that digital inequality operates in layers at the level of physical access, skills gaps, and socio-economic benefits that cumulatively reinforce the existing class structure. The platform society ecosystem is proven to function as a social reproduction engine through three simultaneous mechanisms: algorithmic, habitus, and political economy. This study introduces the concept of digital habitus stratification to explain how class-structured digital dispositions are internalized transgenerationally, and the Platform-Mediated Social Reproduction model as a new analytical framework. The findings also identify the hierarchies of platform capitalism that lock lower-class youth into digital precariatization and class-based segregation of information ecosystems. This research concludes that solutions to digital inequality require transformative-ecological policies that address the broader structural roots of social inequality.